1991
DOI: 10.1111/j.1574-6968.1991.tb04969.x
|View full text |Cite
|
Sign up to set email alerts
|

Dengue haemorrhagic fever and dengue shock syndrome: are they tumour necrosis factor-mediated disorders?

Abstract: A consecutive series of 24 patients with clinical features of primary dengue infection and 22 controls (14 patients with viral fever of unknown origin and 8 healthy subjects) were assayed for serum levels of tumour necrosis factor (TNF). The acute sera of the 24 patients with clinical dengue infection were positive for dengue virus‐specific IgM antibody. Clinically, 8 had dengue fever (DF), 14 dengue haemorrhagic fever (DHF) and 2 dengue shock syndrome (DSS). All 16 patients with DHF/DSS had significantly elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
30
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 23 publications
2
30
0
1
Order By: Relevance
“…5C), suggesting that Fc␥RIIa mediated entry of DV-immune complexes leads to signaling for cytokine production. Cytokine storms are linked to disease severity in severe DV infections, e.g., high serum levels of TNF-␣ in patients suffering from DHF/DSS (52). Identifying a new cellular compartment susceptible to ADE with a capacity for increased viral replication and proinflammatory cytokine release at PENT links key pathogenesis concepts.…”
Section: Discussionmentioning
confidence: 99%
“…5C), suggesting that Fc␥RIIa mediated entry of DV-immune complexes leads to signaling for cytokine production. Cytokine storms are linked to disease severity in severe DV infections, e.g., high serum levels of TNF-␣ in patients suffering from DHF/DSS (52). Identifying a new cellular compartment susceptible to ADE with a capacity for increased viral replication and proinflammatory cytokine release at PENT links key pathogenesis concepts.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be considered that a report has shown augmented serum TNF-␣ levels in patients suffering dengue hemorrhagic fever͞dengue shock syndrome (DHF͞DSS), compared with patients with primary dengue fever (23). While the serum TNF-␣ levels reported for DHF͞DSS patients were a convincing correlate to the severity of these diseases, ex vivo monocyte͞ macrophage cultures from these patients were not examined directly for spontaneous or in vitro stimulated TNF-␣ production, leaving the question open as to the nature of the cells producing the excessive TNF-␣ concentrations in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…TNF is a potent endothelial cell-activating factor with recognized importance in the pathogenesis of severe dengue disease (1, 10). High levels of TNF in DHF patients are suspected of causing activation or injury of endothelial cells (20,38,39,49). Clinical studies of dengue virus-infected patients have repeatedly found high levels of TNF in serum, with increased levels strongly correlated with the severity of disease (16,20,27).…”
mentioning
confidence: 99%